Imeglimin lowers glucose primarily by amplifying glucose-stimulated insulin secretion in high-fat-fed rodents - Perry, Rachel J.; Cardone, Rebecca L.; Petersen, Max C.; Zhang, Dongyan; Fouqueray, Pascale; Hallakou-Bozec, Sophie; Bolze, Sébastien; Shulman, Gerald I.; Petersen, Kitt Falk; Kibbey, Richard G. (American journal of physiology: endocrinology and metabolism, 2016)
Imeglimin is a promising new oral antihyperglycemic agent that has been studied in clinical trials as a possible monotherapy or add-on therapy to lower fasting plasma glucose and improve hemoglobin A 1c (1–3, 9). Imeglimin was shown to improve both fasting and postprandial glycemia and to increase insulin secretion in response to glucose during a hyperglycemic clamp after 1-wk of treatment in type 2 diabetic patients. However, whether the β-cell stimulatory effect of imeglimin is solely or partially responsible for its effects on glycemia remains to be fully confirmed. Here, we show that imeglimin directly activates β-cell insulin secretion in awake rodents without affecting hepatic insulin sensitivity, body composition, or energy expenditure. These data identify a primary amplification rather than trigger the β-cell mechanism that explains the acute, antidiabetic activity of imeglimin.